2010
DOI: 10.3945/jn.110.123505
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects against Oxidized LDL-Induced Breakage of the Blood-Brain Barrier by Lessening Disruption of Tight Junctions and Apoptotic Insults to Mouse Cerebrovascular Endothelial Cells ,

Abstract: Cerebrovascular endothelial cells (CEC) comprise the blood-brain barrier (BBB). In a previous study, we showed that oxidized LDL (oxLDL) can induce apoptosis of mouse CEC. Resveratrol possesses chemopreventive potential. This study aimed to evaluate the effects of resveratrol on oxLDL-induced insults to mouse CEC and its possible mechanisms. Exposure of mouse CEC to 200 μmol/L oxLDL for 1 h did not cause cell death but significantly altered the permeability and transendothelial electrical resistance of the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…Moreover, they demonstrated decreased levels of plasma endothelin-1 and NO, which are increased by hypercholesterolemia. On the other hand, it was also shown that resveratrol protects against injury to the BBB caused by oxidized LDL (oxLDL) (Lin et al, 2010). It is considered that the mechanism behind these effects of resveratrol involves amelioration of the effects of oxLDL on the expression of occludin and ZO-1, which aids the stability of tight junctions.…”
Section: Vasorelaxant Effects Of Polyphenols On Endothelial Cellsmentioning
confidence: 99%
“…Moreover, they demonstrated decreased levels of plasma endothelin-1 and NO, which are increased by hypercholesterolemia. On the other hand, it was also shown that resveratrol protects against injury to the BBB caused by oxidized LDL (oxLDL) (Lin et al, 2010). It is considered that the mechanism behind these effects of resveratrol involves amelioration of the effects of oxLDL on the expression of occludin and ZO-1, which aids the stability of tight junctions.…”
Section: Vasorelaxant Effects Of Polyphenols On Endothelial Cellsmentioning
confidence: 99%
“…A change in morphology, DNA damage, and cell cycle arrest are characteristic features of cells undergoing apoptosis. 13,21,35 In addition, OGD activated caspase-3 in neuro-2a cells. Caspase-3 plays a key role in triggering intrinsic and extrinsic cell apoptosis.…”
Section: Levels Of Nuclear Creb Were Immunodetected (A Upper Panel)mentioning
confidence: 99%
“…When cells undergo apoptosis, specific apoptotic characteristics may appear, including a changed morphology, caspase cascade activation, DNA fragmentation, and cell cycle arrest at the sub-G 1 phase. 21,35 In neuronal development, because apoptosis can precisely regulate the programmed natural death of neurons, it is thought to play important roles in neurogenesis. 14,29 However, premature or irregular apoptotic regulation can lead to the pathogenesis of neurodegeneration, subsequently leading to various acute or chronic brain diseases.…”
mentioning
confidence: 99%
“…Polyphenols are hydrophobic scaffolds exhibiting poor absorption and solubility, resulting in the very short half-life of RSV in the circulatory system (58). Presence of the glycosylated form of RSV is considered to improve physicochemical properties, such as solubility and partition coefficient in order to facilitate the entry of polyphenols into enterocytes (59) and improve bioavailability (60).…”
Section: Biochemistry Of Rsv and Rsv Glucosidesmentioning
confidence: 99%